Repercussão geral - Guimarães Júnior, José Luiz (2008)
The current work aims at studying the requirements which have arisen together with the Constitutional 2004 Reform for appeals to the Supreme Court which consists of showing the relevance as well as transcedency in the subject focused herein. Referred Requirement is also known as General Repercussion. Such studies are justified due to the importance of the subject regarding the profound alteration in a constitutional environment and the legal and regimental changes over them, and how the whole set of bylaws reflected in the Federal Supreme Court as well as in the extraordinary Law System. As to understand these alterations, firstly, we have to analyse the historical and conceptual aspects in the North- American system concerning its influence since the appeals to the Supreme Court genesis. Thus, we move on to the analysis of a similar institutution of remedy qualification named Relevance Allegement which was in full force between 1975 and 1988 in the Brazilian Law System. Going through the necessary historical events, we move to the inspection of different implications from the gradual adoption of law precedents until its binding effect in the current Law System and how the concepts and especificalities of Relevance Allegement, together with those of the Relevance Allegement, are necessary to the theoretical understanding of vague concept and the judicial discricionariety. At last, the procedimental issue is shown from the legislation and update of the subject concerning the Federal Supreme Court. The goal of this current work is to understand the institute which names it from the systematization of various historical, conceptual, and practical aspects able to illustrate an important convergency between the Civil Law and the Common Law traditions as well as the conjugation of these factors that contributed to the allignment precipuos purpose of the Federal Supreme Court as one of an essencial constitutional Court